The art of being brilliant : transform your life by doing what works for you - Cope, Andrew, 1966- (Capstone Publishing Ltd. A Wiley Company, 2012)
A pep talk in your pocket This short, small, highly illustrated book will fill you to the brim with happiness, positivity, wellbeing and, most importantly, success! Andy Cope and Andy Whittaker are experts in the art of happiness and positive psychology and The Art of Being Brilliant is crammed full of good advice, instructive case studies, inspiring quotes, some funny stuff and important questions to make you think about your work, relationships and life. You see being brilliant, successful and happy isn't about dramatic change, it's about finding out what really works f.